New Strategies for Activation of Phosphonates/Phosphates to Forge Functional Phosphorus Compounds - Huang, Hai; Kang, Jun Yong (Synlett, 2019)
Organophosphonate analogues are important structural motifs that are present in bioactive natural products, pharmaceuticals, and agrochemicals. Because they are useful in a broad range of applications, much effort has focused on developing efficient synthetic methods that enable access to organophosphonates and their derivatives. However, currently available synthetic procedures rely on harsh reaction conditions and are limited to a narrow substrate scope. Our lab has recently made important advances in leveraging inert phosphonates/phosphates into functional phosphorus compounds such as mixed phosphonates, phosphates, and mixed aryl phosphate derivatives. Presented herein is an overview of recent achievements in the synthesis of phosphonate/phosphate derivatives and a summary of our recent accomplishments in Tf2O-promoted activating strategy of phosphonate analogues.1 Introduction2 Direct Activating Strategy of Phosphonate Analogues3 Late-stage Phosphonylation of Natural Compounds4 Potential Applications5 Summary
Keywords: phosphorylation; phosphonate; phosphate; phosphinate; mixed phosphonate; mixed phosphate; triflic anhydride